Resolution of Crizotinib-Associated Fulminant Hepatitis following Cessation of Treatment - Gregory W. Charville; Sukhmani K. Padda; Richard K. Sibley; Ajithkumar Puthillath; Paul Y. Kwo (Case Reports in Hepatology)
Targeted cancer treatments offer the prospect of precise inhibition of tumor growth without the untoward off-target toxicity of traditional chemotherapies. Still, unintended, often idiosyncratic side effects, such as drug-induced liver injury, can occur. We discuss the case of a 26-year-old female with a history of ROS1-rearranged lung adenocarcinoma, undergoing treatment with the tyrosine kinase inhibitor crizotinib, who presented to our hospital with abdominal pain and scleral icterus. Liver chemistries were notable for hyperbilirubinemia (5 mg/dL total) and marked transaminasemia (AST 1736 U/L, ALT >3500 U/L); liver biopsy demonstrated acute hepatitis with extensive necrosis. There was no evidence of an infectious or autoimmune etiology. It was discovered that the patient was taking a 500 mg once daily dose of crizotinib, in lieu of the intended dose of 250 mg twice daily. After immediate cessation of crizotinib therapy upon hospital admission, there was complete biochemical resolution of the hepatitis. This case highlights the potential reversibility of fulminant crizotinib-associated hepatoxicity, possibly related to supratherapeutic dosing, when managed with abrupt stoppage of the drug and initiation of supportive care.